Serum neurofilament heavy chains as a biomarker of neuronal damage in multiple sclerosis relapse - Beliaziūnas, P.; Godelienė , R.; Malcienė , L.; Natkevičius , V.; Gintauskienė , V.; Šitkauskienė , B.; Malciūtė , M. (Neurologijos seminarai, 2021)
Introduction. One of the newest methods that could facilitate the diagnosis and treatment of multiple sclerosis is the measurement of neurofilament levels in the blood and spinal fluid. Neurofilament chains can be found not only in multiple sclerosis but also in other neurodegenerative diseases. Latest research findings have revealed that neurofilament levels in serum along with magnetic resonance imaging and clinical evaluation could help evaluate disease relapses and prognosis. No research on neurofilament levels in multiple sclerosis patients has been done in Lithuania so far.Methods. Permit No. BE-2-73 was obtained from Kaunas Regional Biomedical Research Ethics Committee. Using random sampling we examined 28 patients with relapsing-remitting multiple sclerosis who were treated for relapse in the Multiple Sclerosis Centre of Klaipėda University Hospital. Demographic and clinical data and disease modifying therapies were evaluated. Neurofilament heavy chains levels in the blood were measured using ELISA immunoenzyme assay.Results. The research involved 28 patients: 64.3% women and 25.7% men. Neurofilament heavy chains levels in the blood were higher in patients with 3 or more functional systems affected, compared with patients with only pyramidal or cerebellar systems damaged but the difference was not statistically significant. Significantly higher neurofilament heavy chains levels were found in patients with hyperintense magnetic resonance imaging T2 lesions in both brain and spinal cord areas and with contrast-enhanced lesions. Higher neurofilament heavy chains levels were associated with positive oligoclonal bands and prolonged visual evoked potentials. No significant correlation between disease duration, age, disability, and neurofilament heavy chains levels was found. Patients with no disease modifying treatment had higher serum neurofilament heavy chains levels but the difference was not statistically significant.Conclusion. We found higher serum neurofilament heavy chains levels in patients with 3 and more functional systems affected, radiological disease activity, positive oligoclonal bands, and prolonged visual evoked potentials. These results support the hypothesis that neurofilaments could be a promising biomarker for evaluation of multiple sclerosis relapse and disease prognosis in clinical practice.
Keywords: neurofilament; multiple sclerosis; relapse; neurodegeneration